Theories of international cooperation and the GATT/WTO regime: beyond the dichotomy of rational and cognitive approaches - Nischalke, Tobias Ingo (Rhodes University, Faculty of Humanities, Department of Political Studies, 1997)
This thesis aspires to assess the explanatory value of different theories of international cooperation for the case of the world trade regime of GATT/WTO and subsequently strives to reach a satisfactory interpretation of the instance of cooperation. The world trade regime embarked on a process of transformation with the signing of the Marrakech Agreements of 15th April 1994. The event marked the conclusion of the Uruguay Round and, with the establishment of the WTO, the beginning of a new era for the world trade regime. The thesis endeavours to establish the substance of the regime change from GATT to the WTO. It outlines the most significant provisions of the agreement of the Uruguay Round and, subsequently, analyses the change on the level of regime norms underlying the world trade regime. The analysis of regime norms yields insights about the essence of the regime transformation and as to what factors proved to be conducive to cooperation in the sphere of the world trade. The GATT/WTO regime with its extended scope and more sophisticated institutional structures can be regarded as a prime example of successful cooperation. However, the prospects for cooperation between states in an anarchic environment without central authority for enforcement are the subject of a remarkably intense scholarly debate. Therefore it is worthwhile to examine which theoretical framework proves to be most adept at elucidating the circumstances of this instance of cooperation. This thesis applies different theories of international cooperation to the case of the GATT/WTO regime. While a large array of rational theories attempts to explain cooperation from a perspective which focuses on interests and capabilities, a different strand of theories, that of cognitive approaches, emphasizes the paramountcy of ideas and beliefs as variables which explain cooperation. They endogenize the process of interest formation. This thesis seeks to synthesise the strong points of rational and cognitive approaches and thus to reconcile the divergent schools of thought. Its further purpose is to set out factors which are conducive to cooperation.
Keywords: General Agreement on Tariffs and Trade (Organization); World Trade Organization; International trade